Etika Konstitusi dalam Politik Indonesia: Meninjau Kelayakan Gibran Sebagai Wakil Presiden dari Perspektif Hukum Tata Negara - Susanti Susanti (Jurnal Kedaulatan Hukum, 2025)
This article discusses the polemic of Gibran Rakabuming Raka's candidacy as Vice President of the Republic of Indonesia in the 2024 Election through an approach to constitutional law and constitutional ethics. The focus of the study is directed at Constitutional Court Decision No. 90/PUU-XXI/2023 which expands the interpretation of the age requirements for presidential/vice presidential candidates, allowing individuals under 40 years of age to run if they have previously served as regional head. Even though Gibran's candidacy is legally legal, this problem arose because of the close family relationship between the Constitutional Court Judge and the party who benefits, as well as the lack of national leadership experience of the candidate concerned. This research highlights the importance of considering the substantive appropriateness, moral integrity, and neutrality of the judiciary in maintaining the quality of democracy and the supremacy of the constitution. The results of the analysis show that the dominance of a formal legal approach without ethical considerations and leadership capacity can open up space for legal politicization and detrimental constitutional precedents.